Religious Moderation as an Effort to Build Generation Z Tolerance in the Social Media Era : (Moderasi Agama untuk Membangun Toleransi Generasi Z di Era Media Sosial) - Harahap, Nahdah Faizah; Nurhayati, Nurhayati (Journal of Islamic Education and Intellectual Discourse (JIED), 2026)
The development of digital technology has formed a new social ecosystem for Generation Z, which is a group that was born and grew up in social media culture. In Indonesia, social media is not only a means of communication, but also an arena for religious articulation, identity formation, and reproduction of Islamic discourse. This condition makes Generation Z vulnerable to exposure to unbalanced religious information, especially intolerant content, hate speech, and digital radicalism. Religious moderation is present as an alternative strategy to build an inclusive, tolerant, and proportionate religious perspective. This article examines in depth the role of religious moderation in building Generation Z tolerance in the social media era. The research method used is a literature study by analyzing eleven scientific articles from accredited national journals and relevant academic documents. The results of the study show that social media has two faces: as a space for the reproduction of intolerance as well as a potential space to mainstream religious moderation. With the right strategies such as moderate digital literacy, creative da'wah content, and collaboration across religious moderation institutions, it can be an important foundation to strengthen Generation Z's tolerance in dealing with religious diversity in the digital era